Ultrasound propagation in bond frustrated HgCr₂S₄ spinel in magnetic fields - Felea, V.; Prodan, L.; Stefanet, E.; Cong, P.T.; Zherlitsyn, S.; Tsurkan, V. (Физика низких температур, 2017)
Ultrasound and magnetization studies of bond frustrated spinel HgCr₂S₄ are performed as a function of temperature in static magnetic fields. Beside the anharmonic effect, the sound velocity shows pronounced anomaly at the antiferromagnetic (AFM) transition at TN = 23 K with an additional significant increase of the order of 0.5% indicating a strong spin-lattice coupling. External magnetic fields enhance the ferromagnetic (FM) correlations and shift the anomalies to lower temperatures concomitantly with the reduction of the Néel temperature. The constructed H– T phase diagram beside the long-range AFM states reveals the state with induced FM order and regimes with short-range AFM and FM correlations as well.